2002
DOI: 10.1101/gad.1013302
|View full text |Cite
|
Sign up to set email alerts
|

Specification of the mammalian cochlea is dependent on Sonic hedgehog

Abstract: The mammalian inner ear is a complex sensory organ comprised of auditory and vestibular structures that serve to coordinate the senses of hearing and balance, respectively. The inner ear develops over a protracted period originating from a thickening of surface ectoderm, the otic placode, which forms at the level of the prospective hindbrain upon inductive influences from neighboring tissues (Groves and Bronner-Fraser 2000;Ladher et al. 2000). Once induced, the otic placode invaginates to form the otic cup and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
349
1
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 232 publications
(362 citation statements)
references
References 58 publications
(70 reference statements)
10
349
1
2
Order By: Relevance
“…Whereas Hh signaling in zebrafish plays an important role in anteroposterior patterning, in mouse and chicken, it appears to play a different role. Loss of Hh signaling in mouse, as seen in the Shh knockout, results in loss of ventral molecular markers and structures, such as the cochlea and cochleovestibular (otic) ganglion, whereas ectopic activation of Hh signaling dorsally results in down-regulation of dorsal markers and the turning on of some ventral markers (Riccomagno et al, 2002). Hh signaling is also important for inhibiting the expression of more dorsal genes, such as Wnt, ventrally (Riccomagno et al, 2005;Ohyama et al, 2006).…”
Section: Hedgehog Inhibition Results In Mirror Duplicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas Hh signaling in zebrafish plays an important role in anteroposterior patterning, in mouse and chicken, it appears to play a different role. Loss of Hh signaling in mouse, as seen in the Shh knockout, results in loss of ventral molecular markers and structures, such as the cochlea and cochleovestibular (otic) ganglion, whereas ectopic activation of Hh signaling dorsally results in down-regulation of dorsal markers and the turning on of some ventral markers (Riccomagno et al, 2002). Hh signaling is also important for inhibiting the expression of more dorsal genes, such as Wnt, ventrally (Riccomagno et al, 2005;Ohyama et al, 2006).…”
Section: Hedgehog Inhibition Results In Mirror Duplicationsmentioning
confidence: 99%
“…This finding contrasts with the role of Hh signaling in mouse inner ear development, where Sonic hedgehog (Shh) plays a role in dorsoventral patterning by promoting ventral identity and restricting Wnt genes to the dorsal region (Riccomagno et al, 2002(Riccomagno et al, , 2005Ohyama et al, 2006). In chickens, Shh has also been shown to be important for ventral patterning of the otocyst (Bok et al, 2005).…”
Section: Introductionmentioning
confidence: 85%
“…Neither Shh nor Foxa2 was down-regulated in the pharyngeal endoderm or head mesenchyme, and two further pieces of evidence suggest that it is unlikely that the RA repression of Tbx1 in pharyngeal endoderm is mediated by a decrease in expression of Shh or Foxa2. Firstly, axial expression of Shh exerts a long-range signaling effect upon the otic vesicle, but in Shh null mice, Tbx1 expression in the otic epithelium is maintained (Riccomagno et al, 2002), whereas in RA bead experiments otic Tbx1 is completely lost. Secondly, pharyngeal expression of Tbx1 is abnormal in the VAD quail at all stages, but expression of Shh is normal at stage 11 in the presumptive second pharyngeal pouch (Quinlan et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Identifying possible upstream signaling molecules and downstream targets for this transcriptional factor, whether they are epithelium-or mesenchyme-derived, will be important. It is interesting that, in the Shh mutants, both Brn4 and Tbx1 are down-regulated in the otic mesenchyme (Riccomagno et al 2002). The otic capsule is reduced in Shh mutants, indicating that other molecular pathways that mediate otic chondrogenesis are not perturbed by the loss of Shh.…”
Section: Genes Expressed In the Mesenchymementioning
confidence: 94%
“…The delamination of neuroblasts from the anteroventral region of the otic cup or otocyst is also affected in these mutant ears. Even though it has been postulated that SHH released from the ventral midline patterns the inner ear (Riccomagno et al 2002), the presence of low levels of Shh within the otic epithelium has been reported (Liu et al 2002). Although the source of SHH for patterning the inner ear remains an open question, it is clear that the otic epithelium responds directly to SHH as indicated by the presence of Patched (receptor for Shh) and Gli1 (a downstream target of Shh) mRNA transcripts within the epithelium (Liu et al 2002;Riccomagno et al 2002).…”
Section: Genes Expressed In the Hindbrainmentioning
confidence: 99%